2021
DOI: 10.21203/rs.3.rs-858145/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Domestic Violence During the COVID-19 Confinement: Do Victims Feel more Socially Isolated?

Abstract: Background Since March 13th 2020, confinement measures have been introduced in Belgium to curb the spread of the coronavirus (COVID-19). These measures also have an impact on people’s daily life (closure of school/businesses, teleworking, recommendation to stay at home…). This can cause stress on social, economic and psychological levels and thereby can trigger domestic violence. Besides, confinement also fosters social isolation, which can complicate help seeking behaviour. The aim of this study is to determ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The prevalence of childhood obesity has increased dramatically worldwide since 1980 and is considered one of the most serious public health issues [8]. In Flanders, in 2018, it was observed that 16.2% of young people (2-17 years) were overweight and 4.6% of young people suffered from obesity [9]. About 19.4% of people in Flanders drank sugar sweetened beverages daily and 4.1% of people drank at least 1 L of those drinks daily in 2018 [10].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of childhood obesity has increased dramatically worldwide since 1980 and is considered one of the most serious public health issues [8]. In Flanders, in 2018, it was observed that 16.2% of young people (2-17 years) were overweight and 4.6% of young people suffered from obesity [9]. About 19.4% of people in Flanders drank sugar sweetened beverages daily and 4.1% of people drank at least 1 L of those drinks daily in 2018 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Increases in body weight and BMI are described over the life course [10,34]. However, parenthood has been suggested as influential on weight gain for women and men [10], and increases in BMI over time have been described as 17% greater for parents compared with non-parents [15].…”
Section: Discussionmentioning
confidence: 99%
“…The estimates of chronic pain prevalence are up to 20%–25% in some countries and regions (Jackson et al, 2014). For example, in 2018, one in four people in Belgium (ages 15 and up) experienced severe physical pain, which meant a significant increase in the prevalence of chronic pain compared to 2013 (Drieskens & Charafeddine, 2019). This increase is a global phenomenon.…”
Section: Introductionmentioning
confidence: 99%